When marketing misses a trick: Failure to spread word about firm's successes. Issue 11 (7th October 2014) - Unknown
Abstract : Purpose: – This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: – This briefing is prepared by an independent writer who adds his own impartial comments and places the articles in context. Findings: – The piece discusses the gains derived from Lean Six Sigma projects at a UK food manufacturing site and identifies gaps in potential benefits, in particular how well any potential marketing messages were exploited by the organization. The findings critically evaluate the impact that marketing function involvement could have in helping to promote the wider productivity message and its contribution to the wider corporate social responsibility (CSR) strategy for the organisation. Practical implications: – The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value: – The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.